Method based on layered programming to generate code automatic from the class diagram - Vega Fajardo, Adolfo Hans (2020)
The greatest effort in the development of web applications is focused on the generation of code manually based on a programming language. On the other hand, research works focus on solving design problems, while CASE tools generate limited or incomplete codes without formal specifications for web application development. This article proposes a method based on layered programming to generate code automatically from the UML class diagram for web applications. In this way, the class diagram file is analyzed and the respective code is generated. A design model has been defined as a meta-model, which has the formalism of layered programming and is represented by a profile with XML extension, in this way, the lines of XML code are extracted from the file that contains the diagram of classes, are compared with the meta-model through algorithms and then the code is generated automatically. To validate the proposal, an application completed with the objective of comparing between the process of automatic code generation and manual code generation was used, resulting in the code generation being reduced by up to 98%.